Desenvolvimento de sensores e imunossensor eletroquímico para detecção de analitos relacionados à doença de Parkinson - Oliveira, Gabriela Carolina Mauruto de (Universidade Federal de São Carlos, 2019)
The evolutions that have arisen in the medical field, over the last few years, reflect in reliable, accessible and fast response technologies aimed at with problems that are very complex and expensive. Point-of-care and wearable technologies spearhead these innovations, seeking flexible devices who fit the several detection scenarios. The search for new easy access materials and handling as well as a low-cost have been investigated in the electrochemical field. In this work, two electrochemical sensors were developed on flexible nitrile glove and flexible adhesive tape, using the screen printing technique for the deposition of graphite conductive ink. Also, a sensor and an immunosensor were constructed by photolithography and platinum cathodic sputtering, on BioPET sheets. Glove and adhesive tape sensors were evaluated by voltammetry in the presence of biological markers related to Parkinson's disease, using linear voltammetry and differential pulse voltammetry, respectively, for characterization and detection of dopamine and hemoglobin. For dopamine, there were linear ranges between 5.0 x 10 -6 to 1.0 x 10 _4 mol L_1 and 5.0 x 10 _6 to 5.0 x 10 _5 mol L_1, respectively, for glove and adhesive and detection limits of 4.2 x 10 ~1 and 7.2 x 10 ~1 rnolL-1. with successful application in synthetic urine samples. Hemoglobin was detected on adhesive tape, a linear range of 1.0 to 10 mg mL_1 and a detection limit of 0.77 mg mL_1 was obtained. The platinum electrodes was used for a dopamine detection and an immunosensor for a PARK7 / DJ-1 protein. Self-assembled monolayers (SAM) were formed using cystamine and glutaraldehyde to anti-PARK7 / DJ-1 antibody immobilization on the platinum electrode surface. Interface optimizations of interaction time and concentration were performed and the EIS technique was used as an electrochemical technique to detect PARK7 / DJ-1 protein, obtaining a working range between 40 and 175 ngrnL-1 and a limit of detection of 7.5 ng mL-1. Mechanical stress tests were applied in the screen-printed electrodes and platinum electrodes, and both showed good reproducibility of the electrochemical response after twisting, proving the glove and adhesive tape flexibility. The glove and adhesive tape electrodes showed to be an interesting alternative as wearable sensors, innovating in the incorporation of flexible materiais routine. The platinum electrode was a useful device for the construction of biosensors, enabling an effective immobilization of the biological elements on its surface.
Development of a sensor and electrochemical imunosensor for detection of analytes related to Parkinson disease
Keywords: Eletrodo vestível; Imunossensor eletroquímico; Hemoglobina; Doença de Parkinson; Wearable electrodes; Electrochemical imunosensor; Hemoglobin; Parkinson's disease; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA